2018
DOI: 10.1111/iwj.13056
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for surgical site infection after open reduction and internal fixation of intra‐articular fractures of distal femur: A multicentre study

Abstract: There remains a lack of data on the epidemiological characteristics of surgical site infection (SSI) following the open reduction and internal fixation (ORIF) of intra‐articular fractures of distal femur, and the aim of this study was to solve this key clinical issue. The electronic medical records (EMRs) of patients who underwent ORIF for distal femoral fracture from January 2013 to December 2017 were reviewed to identify those who developed a SSI. Then, we conducted univariate Chi‐square analyses and used a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
20
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 30 publications
8
20
0
7
Order By: Relevance
“…Our present study of 364 patients indicated that the total incidence of SSI after ORIF for DFFs was 6.0% at the one-year follow-up, which is consistent with a retrospective multicentre analysis of 724 patients with a two-years follow-up [15]. After adjusting for confounding variables, open fracture, drain use, incision cleanliness and A/G level were demonstrated to be signi cantly associated with SSIs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our present study of 364 patients indicated that the total incidence of SSI after ORIF for DFFs was 6.0% at the one-year follow-up, which is consistent with a retrospective multicentre analysis of 724 patients with a two-years follow-up [15]. After adjusting for confounding variables, open fracture, drain use, incision cleanliness and A/G level were demonstrated to be signi cantly associated with SSIs.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the odds ratio of open fracture was 7.3 in multivariate analysis models. The prevalence of SSI after open DFFs treated by ORIF in our study was 19.8% (17/86), which was in the range from 10.4% to 20.0% according to previous studies on lower limbs[6,12,15]. However, Lu and his colleague reported that the prevalence of SSI after open intra-articular fractures of the distal femur treated by ORIF decreased to 10.…”
supporting
confidence: 40%
See 1 more Smart Citation
“…Our present study of 364 patients indicated that the total incidence of SSI after ORIF for DFFs was 6.0% with one-year follow-up, which was consistent with a retrospective multicentre analysis of 724 patients with a two-year follow-up [15]. We con rmed that S. aureus was the most frequently isolated pathogen of SSIs; patients with an SSI had a signi cantly longer postoperative stay than those without an SSI (45.5 vs…”
Section: Discussionsupporting
confidence: 89%
“…Hoffmann et al identi ed open injury and current smoking as associated risk factors [6]. Lu et al added obesity and diabetes mellitus to the SSI-related predictors [15].…”
Section: Introductionmentioning
confidence: 99%